Approximation of (ψ, β)-differentiable functions by Weierstrass integrals - Kalchuk, I. V.; Kharkevych, Yu. I. (Ukrains’kyi Matematychnyi Zhurnal, 2007)
Asymptotic equalities are obtained for upper bounds of approximations of functions from the classes C^ψ_β ∞ and L^ψ_β 1 by the Weierstrass integrals.